Directional characteristic of a circular membrane vibrating under the effect of a force with uniform surface distribution - RDZANEK, Witold (Archives of Acoustics, 1985)
In this paper the acoustic pressure of a circular membrane is analysed on the assumption that the distance between the field point and the membrane is much longer, both in terms of its linear dimensions and the wavelengths radiated. It was assumed that the membrane was excited to induced harmonic vibration - including nonresonance one - by a force with uniform surface distribution. The membrane was placed in a rigid, planar baffle, and the gas medium, into which it radiated, was 108s1088. Numerical examples of the directional characteristic were represented graphically.